Digital Theology and Social Media in Church Ministry - Rogate Artaida Tiarasi Gultom; Dapot Damanik; Sipahutar, Melina (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
In this context, social media plays a very important role as a new space for religious people to discuss, share knowledge, and expand religious networks and communities globally. Platforms such as Facebook, Instagram, Twitter, YouTube, and blogs have become public spaces where religious teachings and understanding can be received, discussed, and translated into everyday life. With the existence of social media, the concept of a place of worship is no longer limited to churches, mosques, or other physical places of worship, but has expanded to cyberspace which can be accessed by anyone, anytime, and anywhere. The development of digital technology and social media has brought about major changes in various aspects of human life, including religious life. The church, as an institution that plays an important role in spreading the gospel, faces new challenges and opportunities along with the increasing use of digital technology in everyday life. Social media, which is now an integral part of modern communication, provides a new means to convey religious messages and expand the reach of the spread of the gospel. This study will discuss the role of digital theology and social media in spreading the gospel as well as the challenges and opportunities faced by the church in maintaining theological integrity in the digital era. This discussion will cover theological perspectives, the benefits and risks of using social media, and how the church can respond to these technological developments wisely and in accordance with Christian teachings.